Polyacrylonitrile fiber‐based heterogeneous catalysts for organic transformations. Issue 27 (14th July 2022) - Zhang, Juntao; Li, Pengyu; Yang, Yu; Ai, Wenying; Liu, Yuanyuan; Zhang, Wenqin
Abstract: Heterogeneous catalysis is an important way to realize green chemistry. Developing excellent heterogeneous catalysts by using appropriate supports is still a mainstream research area. Polyacrylonitrile fiber (PANF), a common textile material in our daily life, has excellent advantages of low cost, high strength, light density, mildew resistance, etc . Furthermore, PANF can be knitted into varieties of shapes, making them very suitable for fixed‐bed catalysis in industries. Consequently, PANF is a fine raw material for the synthesis of heterogeneous catalysts. Therefore, more and more PANF‐based heterogeneous catalysts had been developed and applied to various of reaction systems. In this paper, the research progress of PANF‐based catalysts was reviewed, and the research progress of different PANF catalytic systems and their applications in green chemistry were emphatically introduced, which provided reference to the development of PANF‐supported catalytic technology. Finally, the catalytic system supported by PANF is summarized and prospected. Abstract : Polyacrylonitrile fiber (PANF), a common textile material in our daily life, which is a fine raw material for the synthesis of heterogeneous catalysts. More and more PANF‐based heterogeneous catalysts have been developed and applied to organic transformations. In this paper, the research progress of PANF‐based catalysts was reviewed, and the research progress of different PANF catalytic systems and their applications in green chemistry were emphatically introduced, which provided references for the development of PANF‐supported catalytic technology.